Tinnitus and sleep difficulties after cochlear implantation - Pierzycki, Robert H.; Edmondson-Jones, Mark; Dawes, Piers; Munro, Kevin J.; Moore, David R.; Kitterick, Pádraig T. (Lippincott, Williams & Wilkins, 2016)
OBJECTIVES: To estimate and compare the prevalence of and associations between tinnitus and sleep difficulties in a sample of UK adult cochlear implant users and those identified as potential candidates for cochlear implantation. DESIGN: The study was conducted using the UK Biobank resource, a population-based cohort of 40- to 69-year olds. Self-report data on hearing, tinnitus, sleep difficulties, and demographic variables were collected from cochlear implant users (n = 194) and individuals identified as potential candidates for cochlear implantation (n = 211). These "candidates" were selected based on (i) impaired hearing sensitivity, inferred from self-reported hearing aid use and (ii) impaired hearing function, inferred from an inability to report words accurately at negative signal to noise ratios on an unaided closed-set test of speech perception. Data on tinnitus (presence, persistence, and related distress) and on sleep difficulties were analyzed using logistic regression models controlling for gender, age, deprivation, and neuroticism. RESULTS: The prevalence of tinnitus was similar among implant users (50%) and candidates (52%; p = 0.39). However, implant users were less likely to report that their tinnitus was distressing at its worst (41%) compared with candidates (63%; p = 0.02). The logistic regression model suggested that this difference between the two groups could be explained by the fact that tinnitus was less persistent in implant users (46%) compared with candidates (72%; p < 0.001). Self-reported difficulties with sleep were similar among implant users (75%) and candidates (82%; p = 0.28), but participants with tinnitus were more likely to report sleep difficulties than those without (p < 0.001). The prevalence of sleep difficulties was not related to tinnitus persistence (p = 0.28) or the extent to which tinnitus was distressing (p = 0.55). CONCLUSIONS: The lack of association between tinnitus persistence and sleep difficulties is compatible with the notion that tinnitus is suppressed in implant users primarily during active electrical stimulation and may return when the implant is switched off at night time. This explanation is supported by the similar prevalence of sleep problems among implant users and potential candidates for cochlear implantation, despite differences between the groups in tinnitus persistence and related emotional distress. Cochlear implantation may therefore not be an appropriate intervention where the primary aim is to alleviate sleep difficulties.